Nickel percolation and coarsening in sintered Li4Ti5O12 anode composite. Issue 8 (7th May 2020) - Huddleston, William; Dynys, Frederick; Sehirlioglu, Alp
Abstract: Inherently safe all‐solid‐state lithium‐ion battery anodes with high electronic and ionic conductivity are sought to enable next‐generation electric propulsion systems. In novel architectural concepts, multifunctionality of battery materials will provide simultaneous mechanical load bearing and electrochemical energy storage functionality for systems level mass savings. Co‐processing of strain‐free lithium titanate anode and nickel current collector was explored to provide structural integrity and electrical conductivity for a load‐bearing anode with bulk current collection capability. In this study, the effects of processing conditions on densification, electrical conductivity, and microstructural evolution were characterized for Li4 Ti5 O12 ‐Ni (LTO‐Ni) composites. Densification of LTO‐Ni was achieved at 900°C and above, and nickel content had minimal effect on final density compared to sintering temperature and time. Electronic conductivity was modeled by percolation theory, exhibiting a large dependence on nickel content and bulk density. Bulk electrical conductivity greater than 1 S/cm was achieved at volume fractions above the percolation threshold. Modeling of microstructural evolution applied Ostwald ripening theories to describe diffusion governing the growth of average nickel particle size and the change in size distributions. Volume fraction effects resulted in larger average Nickel particle sizes and an activation energy of 1.04 eV was measured for nickel particle coarsening.